Does cervical cerclage decrease preterm birth in twin pregnancies with a short cervix?. (18th April 2018) - Adams, Tracy M.; Rafael, Timothy J.; Kunzier, Nadia B.; Mishra, Supriya; Calixte, Rose; Vintzileos, Anthony M.
Abstract: Purpose: To determine if use of cerclage in twin gestations with mid-trimester short cervix is associated with decreased preterm birth rate. Study design: This is a retrospective cohort of twin gestations identified with cervical length of ≤2.5 cm before 24 weeks of gestation through the perinatal ultrasound database of two institutions from 2008 to 2014. Patients with and without cerclage were compared for a primary outcome of preterm birth at <35 weeks. A pre-planned sub-group analysis of patients with cervical length ≤1.5 cm was also performed. Results: Eighty-two patients were included; 43 received cerclage, 39 did not. Mean gestational age at cerclage placement was 20.8 weeks. There was no significant difference in rate of preterm birth <35 weeks between the groups (34.9% versus 48.7%, respectively). In the sub-group analysis of patients with cervical length ≤1.5 cm, there was a significant decreased risk of preterm birth <35 weeks [37% versus 71.4%; adjusted RR 0.49 (0.26–0.93)]. Conclusion: Cerclage placement for cervical length ≤2.5 cm in twin gestations did not decrease the rate of preterm birth at <35 weeks; however, cerclage placement for cervical length ≤1.5 cm was associated with a significantly decreased rate of preterm birth <35 weeks when compared to patients managed without cerclage.